The Socialization Of Terrorism In Canada - John Gilmour (The Journal of Intelligence, Conflict and Warfare, 2024)
The academic and institutional battlefield is littered with the best intentions of those attempting to bring a universally recognized definition to the term ‘terrorism’.  The concept of ‘where you sit is where you stand’ certainly applies to such endeavors.  In addition to considering how best to integrate such fundamental questions as who, what, where, why and how in a definition of the term, attempts have been confounded and complicated by where definitional efforts have been centered within a particular community. Do you adopt a social science or quasi-scientific approach?  From a jurisprudence and law enforcement perspective? Terrorist financing? Intent and motivation? Psychological drivers and personal profiles of individual terrorists? Organizational structures?  Cultural and anthropological approaches? Rationality and mental health? Historical considerations? Critical study interpretations?  All this has made for terrorism being a contested concept over the decades. As observed by Schmid and Jongman, and as we shall explore, “The nature of terrorism is not inherent in the violent act itself. One and the same act can be terrorist or not, depending on the intention and circumstances.”  But how terrorism is defined by whatever community is not a trivial issue. Definitions carry political and policy consequences that govern the counterterrorism space and how threats and risks are articulated going forward.  How the threat environment endures is often just as much an outcome of how a state elects to respond to the threat, as it is the agenda of terrorist entities.  And terrorism charges cannot be prosecuted if there is not at least some notion of how motivations, intentions and acts are defined in statutes.